POLA KOMUNIKASI DALAM PENGEMBANGAN MODAL MANUSIA DAN SOSIAL PERTANIAN (Forum Penelitian Agro Ekonomi, 2024)
This paper aims to analyze the high quality of agricultural human capital and social indicators in improving the performance of national development and to formulate their communication patterns to support capacity building of human and social capital of agriculture in every line of agricultural development.  The lack of agricultural human capital and social capital capacity is one of the constraints causing the accessibility limitation for Indonesian agriculture to face the global competition.  The low farmer’s education attainment has caused a low capacity of farmers to manage information and to adopt new technology resulting the low products quality.  At the extension level, the shortage number and quality of the extension workers has also contributed to that situation.   Beside low of basic capability, most of the extension workers do not have adequate mental capacity, especially related to integrity, communication skills, and moral and ethical capacity.  At the policy maker’s level, many local government institutions have no capacity to mapping agricultural resources along with their capability to make use of the available resources. With the high technical ability, agricultural human resource as a capital resource and as a social resource should have shared values and rules that expressed through personal relationships, trust, and common sense about the community responsibilities. To strengthen agricultural sector In supporting national development, agricultural sector need appropriate communication patterns for agricultural human resource improvement at each level of agricultural development.  Such communication pattern should be based on the convergent-interaction communication through knowledge sharing model.  This model is appropriate for both agricultural personnel and for farmers.  Through active role of various institutions within the Ministry of Agriculture and with the help of modern information technology, a network to reach farmers could be achieved. The extension workers or village facilitators are required in the development of agricultural community because of its important function as problem analyst, group supervisor, trainers, innovators, and liaison officers.